Contrast sensitivity function in Graves' ophthalmopathy and dysthyroid optic neuropathy. - Suttorp-Schulten, M S (1993)
Contrast sensitivity function was measured by a computer automated method on 38 eyes with dysthyroid optic neuropathy and 34 eyes with Graves' ophthalmopathy only. The results were compared with 74 healthy control eyes. Disturbances of contrast sensitivity functions were found in both groups when compared with controls. The eyes affected with dysthyroid optic neuropathy showed pronounced loss of contrast sensitivity in the low frequency range, which facilitates differentiation between the two groups.